PENGARUH KOMPENSASI, DISIPLIN KERJA DAN MOTIVASI TERHADAP PRODUKTIVITAS KARYAWAN PT ESTA DANA VENTURA KOTA PALOPO - Reivaldo; Sukri; Dirham Latif (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to determine the effect of compensation, work discipline andmotivation on employee productivity at PT. Esta Venture Fund Palopo City. To find out the effect of compensation on employee productivity at PT. Esta Venture Fund Palopo City. To find out the effect of work discipline on employee productivity at PT. Esta Venture Fund Palopo City. To find out the effect of motivation on employee productivity at PT. Esta Venture Fund Palopo City. This type of research used quantitative research, the respondents in this research are all employees of PT. Esta Venture Fund Palopo City as much 29 people and data processing using multiple linear regression. Based on research that has been carried out on several tests of the variables studied, the following conclusions can be drawn: The results of the study explained that (1) Simultaneously the variables of compensation, work discipline and motivation have a significant effect on employee productivity at PT. Esta Venture Fund Palopo City. (2) Partially the compensation variable has no significant effect on employee productivity at PT. Esta Venture Fund Palopo City. (3) Partially the variable of work discipline has a significant effect on employee productivity at PT. Esta Venture Fund Palopo City. (4) Partially the motivation variable does not have a significant effect on employee productivity at PT. Esta Venture Fund Palopo City. Keywords : Compensastion, Work Discipline, MotivationandEmployee Productivity